The Urgency and Mechanism for Halal Certification of MSME Products in E-Commerce - Wirdyaningsih, Wirdyaningsih; Syahida, Aufi Qonitatus; Karimah, Iffah; Nabilah, Annisah Marwah (Jurnal Dinamika Hukum, 2021)
The current development of technology supports the use of e-commerce for fulfillment of public needs. Nowadays, more start-ups and digital companies in Indonesia, including Micro, Small and Medium Enterprises (MSME) are targeting sharia market through selling halal goods on e-commerce shop and provide sharia investment products for Muslims. However, the high usage of e-commerce in Indonesia, which has become a necessity for Muslim societies, is not comparable with halal certification on MSME products in e-commerce. Based on the problems, this paper examines the urgency and mechanism of halal certification in MSME products in e-commerce in Indonesia. This research uses juridical-normative research methods to address this issue. Based on the research result, researchers found that coordination with all parties is needed, ranging from the government to the industrial actors, so that all MSME products from e-commerce can easily carry out halal certification. The government needs to form a digital economic interconnection of sharia so that the sharia economy is also not left behind in terms of financial technology, Islamic financial institutions, online commerce, and social finance. Various parties including the Ministry of Trade, the National Sharia Council (DSN) MUI need to make regulations and fatwa in support of halal certification in e-commerce.Â Keywords: e-commerce; halal certification; Indonesian economy; MSME; products.